γδ T Cell in Cerebral Ischemic Stroke: Characteristic, Immunity-Inflammatory Role, and Therapy - Wang, Li; Yao, Chengye; Chen, Jiayi; Ge, Yangyang; Wang, Chenchen; Wang, Yu; Wang, Fuquan; Sun, Yan; Dai, Maosha; Lin, Yun; Yao, Shanglong (Frontiers in Neurology, 2022)
Gamma-delta (γδ) T cells are a small subset of T cells that are reported to have a proinflammatory role in the pathophysiology of cerebral ischemia stroke (CIS). Upon activation by interleukin-1 beta (IL-1β), IL-23 and IL-18, γδ T cells are stimulated to secrete various cytokines, such as IL-17a, IL-21, IL-22, interferon-gamma (IFN-γ), and IL-1β. In addition, they all play a pivotal role in the inﬂammatory and immune responses in ischemia. Nevertheless, the exact mechanisms responsible for γδ T cell proinﬂammatory functions remain poorly understood, and more effective therapies targeting at γδ T cells and cytokines they release remain to be explored, particularly in the context of CIS. CIS is the second most common cause of death and the major cause of permanent disability in adults worldwide. In this review, we focus on the neuroinﬂammatory and immune functions of γδ T cells and related cytokines, intending to understand their roles in CIS, which may be crucial for the development of novel effective clinical applications.